The tribal imagination : civilization and the savage mind - Fox, Robin, 1934- (Harvard University Press, 2011)
Fox traces our ongoing struggle to maintain open societies in the face of profoundly tribal human needs that, paradoxically, hold the key to our survival. This latest book ranges from incest and arranged marriage to poetry and myth, from human rights and vengeance to pop icons such as Seinfeld.